Wealth Distribution and Social Justice in Islamic Economic Law: Normative Principles and Their Implications for Inclusive Development (TAWAZUN: Journal of Sharia Economic Law, 2025)
Global wealth inequality remains a persistent challenge that undermines social justice and inclusive development. Conventional economic systems have struggled to address structural disparities, leading to wealth concentration and social exclusion. This study examines wealth distribution and social justice from the perspective of Islamic economic law, focusing on its normative principles and their implications for inclusive development. Using a qualitative library-based research design grounded in normative legal analysis, this study analyzes primary Islamic legal sources, namely the Qur’an and Hadith, alongside classical and contemporary Islamic legal scholarship. Empirical socio-economic data from international institutions are employed as contextual references to assess the modern relevance of Islamic legal principles. The findings reveal that Islamic economic law conceptualizes wealth not as an absolute individual right but as a trust (amānah) bound by social responsibility. Normative principles such as justice (al-ʿadl), balance (al-mīzān), and social solidarity are institutionalized through legally structured redistributive instruments, including zakat, infaq, ṣadaqah, and waqf, as well as prohibitions against usury and monopolistic practices. These instruments operate through both curative mechanisms that alleviate immediate poverty and preventive mechanisms that restrain excessive wealth concentration. As a result, Islamic economic law provides a multi-layered distributive framework that links social justice with inclusive development. The study concludes that Islamic economic law offers a coherent normative and legal framework capable of addressing structural inequality while promoting inclusive growth. When supported by effective governance and policy integration, its redistributive instruments have significant potential to reduce poverty, foster social cohesion, and promote sustainable development in contemporary societies.